1987
DOI: 10.1002/eji.1830170303
|View full text |Cite
|
Sign up to set email alerts
|

Selective immunosuppression with anti‐interleukin 2 receptor‐targeted therapy: helper and suppressor cell activity in rat recipients of cardiac allografts

Abstract: (LEW X BN)F1 cardiac allografts are rejected within 8 days in unmodified LEW rats. ART18, a mouse anti-rat IgG1 monoclonal antibody which binds specifically in vitro to the interleukin 2 receptor (IL 2R) molecule expressed primarily on activated T cells, prolongs allograft survival in a dose-dependent fashion to ca. 3 weeks (p less than 0.001) after being administered for 10 days after transplantation. This effect was related to the specificity of the antibody for IL 2R, as therapy with ART62 (a monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Our working hypothesis is that because the fi chain of the IL2R is shown to be heavily glycosylated (more than 40% [191) it could be that the glycosylation sites are randomly arranged and therefore certain epitopes which fall into these glycosylation sites are not always accessible to m 4 b which recognize them, while other epitopes being located at a distance from glycosylation sites are more accessible to the corresponding mAb, resulting in different estimations of the numbers of binding sites of mAb shown to recognize the same molecule on the same cell type. It could also be that different T cell subsets could account for the seemingly paradoxical findings reported recently [20], where the mAb ART-18 injected into recipients of allografts eliminated CD4' effector cells but spared some CD8' suppressor cells.…”
Section: Resultsmentioning
confidence: 96%
“…Our working hypothesis is that because the fi chain of the IL2R is shown to be heavily glycosylated (more than 40% [191) it could be that the glycosylation sites are randomly arranged and therefore certain epitopes which fall into these glycosylation sites are not always accessible to m 4 b which recognize them, while other epitopes being located at a distance from glycosylation sites are more accessible to the corresponding mAb, resulting in different estimations of the numbers of binding sites of mAb shown to recognize the same molecule on the same cell type. It could also be that different T cell subsets could account for the seemingly paradoxical findings reported recently [20], where the mAb ART-18 injected into recipients of allografts eliminated CD4' effector cells but spared some CD8' suppressor cells.…”
Section: Resultsmentioning
confidence: 96%
“…It is confirmed that IL2 can enhance the killing activity of macrophages and NK cells, and directly or indirectly regulate T cell as well as B cell differentiation and proliferation (8,11). The immunoregulation of IL2 depends on the expression of specific IL2R (6).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, ART-18 had the maximal number of molecules bound per G2 cell (75,000), followed by OX-39 (61,185), and ART-65 (27,702) . Recent work from this laboratory has demonstrated sparing of Ts by ART-18 treatment (4,12) . Donor-specific test graft survival is prolonged in naive syngeneic rats to 15 .0 ± 1 and 15.5 ± 0 .9 d after adoptive transfer of 100 x 106 unseparated SL or 50 x 106 CD8' T cells harvested from mAb-conditioned animals 10 d after transplantation, respectively (p < 0.001); CD4+ cells (40-50 x 106 ) were ineffectual (8.5 ± 0.5 d) .…”
Section: Resultsmentioning
confidence: 99%
“…Although each mAb interacts specifically with a given epitope in vivo, the three-dimensional structure of the epitope may occur on both related and unrelated molecules (13) . For example, ART-62, a mouse anti-rat IgG1 antibody that blocks T cell function and inhibits II-2-dependent T cell proliferation in vitro, lacks biological activity in vivo, despite recognizing broadly the epitope of the rat MHC Class I antigen present on various cells including erythrocytes (12) . It is The In Vitro and In Vivo Properties of Mouse Anti-rat IL-2-R rnAbs ' The in vitro properties of mAbs were tested using the IL-2-dependent rat G2 T cell line .…”
Section: Discussionmentioning
confidence: 99%